Administrator and Motivation Creation - นวลสิงห, ธันยาภรณ (พาพลงาม); ชาปัญญา, ยุวธิดา; ศีลพันธุ, ชีวรัตน์ (Journal of Roi Et Rajabhat University, 2016)
Motivation is one of important factors affecting human behaviors as it stimulates desires in people to be willing, and committed to a job and make an effort to attain a goal. Currently, government and private’s organizations are interested in feeling of their staff. It is necessary for organizations’ administrators to promote and create motivation to optimize the effectiveness of work performance. Moreover, work motivation can direct an effective administration of effective leaders. Accordingly, administrators or leaders should find out effective techniques to create motivation of their personnel in order to reach organizational goal effectively.